The Influence of Macroeconomics and Financial Performance on the Profitability of Islamic Banking in Indonesia - Muhamad Haris; Nurwahidin Nurwahidin; Veithzal Rivai Zainal; Mohammad Izdiyan Muttaqin (Journal Research of Social Science, Economics, and Management, 2025)
The purpose of this study is to ascertain how Islamic banking's financial performance and macroeconomic conditions affect its profitability. The object of this study is Islamic banking in Indonesia from 2015 to 2024, in the form of Sharia Commercial Banks (BUS) and Sharia Business Units (UUS). The independent variables in this study are macroeconomics which is measured through financial ratios, namely inflation and the Rupiah exchange rate (exchange rate) and for financial performance is measured through financial ratios, namely Financing to Deposit Ratio (FDR), Non-Performing Financing (NPF) and Operating Expenses of Operating Income (BOPO), while the dependent variable, namely profitability is measured through Return on Asset (ROA). The data used is monthly financial statement data for the last 10 years taken quarterly (per 3 months) starting from March 2015 to December 2024. The data was analyzed using multiple regression methods. The NPF and BOPO variables had a somewhat significant impact on ROA, according to the t-test results.  In the meantime, ROA was only marginally impacted by the factors of inflation, exchange rates, and FDR.  The F test findings demonstrated that all of the variables—inflation, exchange rate, FDR, NPF, and BOPO—had a substantial impact on ROA at the same time.